2017
DOI: 10.1177/0956462417726700
|View full text |Cite
|
Sign up to set email alerts
|

Association between eye diagnosis and positive syphilis test results in a large, urban sexually transmitted infection/primary care clinic population

Abstract: In 2015, the Centers for Disease Control and Prevention (CDC) and the American Academy of Ophthalmology (AAO) released clinical advisories on rising cases of ocular syphilis. We examined the association between eye disease and syphilis infection among primary care and sexually transmitted infection (STI) clinic patients attending an urban lesbian, gay, bisexual, transgender (LGBT) health center. We conducted a retrospective medical record review of all patients who underwent syphilis testing at Howard Brown He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…Compared to systemic syphilis, ocular involvement is rare. In this study, ocular syphilis occurs in only 5.1% of total syphilis cases based on a 6 year case series study, which is similar to previous studies reported in literature (1,5,6). Although ocular syphilis mainly occurs in secondary and tertiary syphilis, our study demonstrated that 95.4% of syphilis cases (125/131) had no past medical history, or systemic manifestation of syphilis at presentation, which indicates that most ocular syphilis may present as the only clinical manifestation of syphilis, i.e., most ocular syphilis may occur in latent syphilis (7,8).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Compared to systemic syphilis, ocular involvement is rare. In this study, ocular syphilis occurs in only 5.1% of total syphilis cases based on a 6 year case series study, which is similar to previous studies reported in literature (1,5,6). Although ocular syphilis mainly occurs in secondary and tertiary syphilis, our study demonstrated that 95.4% of syphilis cases (125/131) had no past medical history, or systemic manifestation of syphilis at presentation, which indicates that most ocular syphilis may present as the only clinical manifestation of syphilis, i.e., most ocular syphilis may occur in latent syphilis (7,8).…”
Section: Discussionsupporting
confidence: 91%
“…Although ocular syphilis mainly occurs in secondary and tertiary syphilis, our study demonstrated that 95.4% of syphilis cases (125/131) had no past medical history, or systemic manifestation of syphilis at presentation, which indicates that most ocular syphilis may present as the only clinical manifestation of syphilis, i.e., most ocular syphilis may occur in latent syphilis (7,8). Different from ocular syphilis in developed western countries which frequently occur in HIV positive patients (ranged from 22% to 65%), ocular syphilis was mostly found in HIV negative patients in China and other East-Asian countries (5)(6)(7)(8)(9)(10)(11)(12). In our study, only 2.9% (2/70) of ocular syphilis cases were HIV positive, the prevalence of concurrent ocular syphilis and HIV was similar to that reported in previous investigation from China, indicating that despite a high risk of co-infection in syphilis cases, concurrent HIV infection rate might be low in China (5).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of syphilis, including ocular syphilis, has been on the rise, particularly in men who have sex with men (MSM) and HIV-positive patients. 3 Much of this trend is probably due to the resumption of sexual behaviour since the arrival of ART. 4 When safe-sex practises are used, this is often confined to genital and anal contact; it is widely believed that oral sex is ‘safe’.…”
Section: Discussionmentioning
confidence: 99%